Distinct pathways of homologous recombination controlled by the SWS1–SWSAP1–SPIDR complex - Prakash, Rohit; Sandoval, Thomas; Morati, Florian; Zagelbaum, Jennifer A.; Lim, Pei-Xin; White, Travis; Taylor, Brett; Wang, Raymond; Desclos, Emilie C. B.; Sullivan, Meghan R.; Rein, Hayley L.; Bernstein, Kara A.; et al. (Nature communications, 2021)
Homology-directed repair (HDR), a critical DNA repair pathway in mammalian cells, is complex, leading to multiple outcomes with different impacts on genomic integrity. However, the factors that control these different outcomes are often not well understood. Here we show that SWS1–SWSAP1-SPIDR controls distinct types of HDR. Despite their requirement for stable assembly of RAD51 recombinase at DNA damage sites, these proteins are not essential for intra-chromosomal HDR, providing insight into why patients and mice with mutations are viable. However, SWS1–SWSAP1-SPIDR is critical for inter-homolog HDR, the first mitotic factor identified specifically for this function. Furthermore, SWS1–SWSAP1-SPIDR drives the high level of sister-chromatid exchange, promotes long-range loss of heterozygosity often involved with cancer initiation, and impels the poor growth of BLM helicase-deficient cells. The relevance of these genetic interactions is evident as SWSAP1 loss prolongs Blm -mutant embryo survival, suggesting a possible druggable target for the treatment of Bloom syndrome. Human SWS1, SWSAP1, and SPIDR interact with RAD51, a critical protein for homology-directed repair. Here the authors reveal roles for the mouse SWS1–SWSAP1–SPIDR complex in inter-homolog recombination, including during meiosis, and sister chromatid exchange in BLM helicase deficient cells.